Malignant Hemangiopericytoma Arising in Neurofibromatosis: A Case Report with Histological, Immunohistochemical and Ultrastructural Studies. (1999) - Wang, Jun; Vargas, Hernan; Gaal, Karl; Wang, Xia; Peng, Shi-Kaung
Abstract : Subject. A 27-year-old Hispanic male with clinical manifestation of neurofibromatosis type 1 developed chronic constipation and urination difficulty along with recently increased abdominal bloating and anorexia. He also noted 40 lbs weight loss over period of 1 year. Physical and radiographic examinations revealed a large mass in the right pelvic fossa. Results. The surgically removed tumor was demonstrated, histologically, immunohistochemically, and ultrastructurally, to be a malignant hemangiopericytoma. Discussion. Although non-neurogenic tumors associated with neurofibromatosis have been reported in these patients, only one hemangiopericytoma case has been found in the English literature. We report here another case of this rare malignant hemangiopericytoma in a patient with neurofibromatosis.